Adaptive programming in practice: shared lessons from the DFID-funded LASER and SAVI programmes - Derbyshire, Helen; Donovan, Elbereth (DFID-LASER Programme, 2016)
LASER synthesis papers aim to help donors and other stakeholders bette r understand why and how to approach investment climate reform program ming differently. The papers reflect emerging best practice and lesson s learnt on what works and what does not work in doing development dif ferently. The papers have been peer-reviewed by experts in the field i ncluding senior advisers at DFID, World Bank, IFC and the Donor Commit tee for Enterprise Development (amongst others).
Keywords: IMPORTANT; Practice